Relationship between trace metal concentrations in the terrestrial moss Pseudoscleropodium purum and in bulk deposition. (June 2015) - Boquete, M.T.; Fernández, J.A.; Carballeira, A.; Aboal, J.R.
Abstract: The relationship between trace metal concentrations in Pseudoscleropodium purum (Hedw.) M. Fleish. and bulk deposition (BD) was examined at 21 sites (SS) to ascertain whether the lack of correlations reported in previous studies are due to limitations in the experimental design. Thus, we implemented some improvements to it and examined the correlations in depth. We could conclude that this relationship is determined by other variables rather than by the pollutant inputs themselves (BD). Thus, whether or not moss concentrations and bulk deposition are significantly correlated will depend on the combination of the above referred factors in a given area at a given time. Therefore, P. purum in particular, and most likely native terrestrial mosses in general, are less than ideal biomonitors for yielding absolute values of atmospheric trace metal deposition. We recommend their use as qualitative indicators and the use of classical methods to obtain absolute values. Highlights: Relationship between the concentrations of metals in P. purum and in bulk deposition (BD) was examined. Number of significant correlations was very limited and depended on how the data were analysed. This relationship is mainly determined by factors other than the inputs of the pollutants themselves. Native terrestrial mosses are less than ideal biomonitors for obtaining absolute values of atmospheric deposition. We recommend to use terrestrial mosses as qualitative indicators in biomonitoring studies. Abstract : Atmospheric trace metals deposition does not mainly determine the concentrations of these elements in Pseudoscleropodium purum so that this species cannot be used for obtaining absolute atmospheric trace metal deposition values.